Comparison of Intermediate Fidelity Simulation with PowerPoint Presentation and Video Lectures for Imparting the Skills of Normal Delivery to Undergraduate Students-A Research Protocol - Sandhya Pajai; Swanand Pathak; KS Uplabdh Gopal (Journal of Clinical and Diagnostic Research, 2023)
Introduction: In the modern era, which is heavily driven by multimedia, traditional ways of teaching medical students are insufficient. Techniques based on simulations might be crucial in closing this educational gap that exists. A curriculum built on the cognitive, psychomotor, and emotional learning domains, which were first introduced about 50-year-ago, is receiving more and more attention in medical education. The highest standards of care, patient safety and error prevention, patient autonomy, and resource allocation are the main goals of these reforms. Experiential (or “hands-on”) learning is becoming more and more popular in medical education, however, using real patients to conduct this type of learning raises ethical and legal issues and is less socially acceptable. With the help of simulation, learning possibilities like immersion, reflection, practice, and feedback can be offered without the hazards associated with a similar real-life experience. The precise artificial recreation of a difficult real-world process is called simulation. Need of study: Despite the many benefits of fidelity-based learning, it is not widely incorporated as an excellent learning tool in many institutions and Obstetrics and Gynaecology departments. Hence, authors plan to study the effectiveness of an intermediate fidelity simulator in improving the skills of normal delivery in medical students. Aim: To assess skill development and teaching for normal delivery through PowerPoint presentation and video lectures, then compare it with skill development through Intermediate fidelity simulation in undergraduate medical students. Materials and Methods: The cross-sectional, observational study after due ethical approval will be conducted in Department of Obstetrics and Gynaecology, Acharya Vinoba Bhave Rural Hospital, Jawaharlal Nehru Medical College, Sawangi (M), Wardha, Maharashtra, India from September 2022 to August 2023. An introductory lecture will be taken for a batch of 160 students of 3rd year. Pre-Objective Structured Clinical Examination (pre-OSCE) will be conducted and then two groups of students will be formed. Group A will be taught with video PowerPoint presentation-based lectures meanwhile intermediate fidelity will be used as a method for teaching normal delivery for Group B. Post-OSCE will be conducted for both groups. Results will be analysed using student’s paired t-test for statistical significance.